Staminodes influence pollen removal and deposition rates in nectar-rewarding self-incompatible Phanera yunnanensis (Caesalpinioideae). (26th January 2019) - Wang, Menglin; Huang, Shuyin; Li, Manru; McKey, Doyle; Zhang, Ling
Abstract: Staminodes are sterile stamens that produce no pollen, exhibit diverse structures and perform various functions. Flowers of Phanera yunnanensis possess three fertile stamens with large anthers and long filaments, and seven staminodes with tiny anthers and short filaments. To investigate the adaptive significance of staminodes in this species, we studied effects of staminode removal on pollen removal and deposition, flower visitation rate and fruit set in Xishuangbanna, south-western China. Four species of nectar-foraging pollinators visited flowers, mostly Amegilla zonata and Apis cerana (2.80 ± 0.15 and 1.76 ± 0.41 visits h −1 per flower, respectively). Staminode removal did not affect fruit set, but increased visitation by A. cerana by 2.6-fold, reduced visitation by A. zonata by 68% and increased the pollen removal rate for both pollinators (all effects were significant). Staminode removal significantly reduced pollen deposition rate for A. zonata, but not for A. cerana . These results suggest that the staminodes of P. yunnanensis filter which insects act as pollinators and affect pollen removal and deposition rates. By reducing pollen removal rates, staminodes may implement a pollen-dispensing schedule that spreads pollen dispersal from individual flowers over multiple pollinators. By altering pollen deposition rates, staminodes may influence reproductive fitness in other ways.